An Analysis of Abbreviation on the University Students’ Speech - Muhammad Rinzat Iriyansah; Syahyuri Syahyuri; Nico Harared (Scope : Journal of English Language Teaching, 2023)
Abbreviations are often used to save time and space in writing or speech and become a trend of communication. They are created by taking the initial letters or syllables of a longer word or phrase and forming a compact representation of it. Abbreviations are commonly used in various fields such as education, medicine, science, and technology, and the most common usage is in everyday communication. This study aims to find out the type of abbreviation formation carried out by Sultan Ageng Tirtayasa University students during their communication. This study used a qualitative descriptive method due to the researchers described the analysis in the form of sentence. The data was taken from the students’ communication in terms of recording. The results show that there are 4 classifications of abbreviation used by Sultan Ageng Tirtayasa University students, namely acronyms which are obtained at 35.3%, shorthand which is 42.2%, fragments are 14%, and contractions which are 8,5%. No abbreviation is found in the form of a crest.